Lifelong Learning Courses – Not Just an Alternative Way - Zeman, T.; Hrad, J. (Elektronika ir Elektrotechnika, 2010)
The situation of engineering education at technical universities in Central European countries has been recently complicated by several factors, including financial recession, decreased interest in technical science, and lower total number of young people who could become students. These circumstances imply financial problems of the universities (especially public ones), but also forces the teachers to turn to different activities, methods and target groups, for example distance and lifelong education that can become very important in the near future. The purpose of this paper is to introduce specific projects focusing on distance education in the areas of automation and electronic communications, their partial results and possible exploitation of their outputs by partners in various European countries.